The meaning of democratic education: revisiting the concept of educative experience in John Dewey (Educação e Pesquisa, 2010)
Understanding the modernity of Dewey's pedagogical proposal requires a careful appraisal of his concept of educative experience. Actually, his educational philosophy is grounded on a theory of experience, insofar as it rests upon a connection between personal experience and learning whose aim is the progressive enlargement of that experience. In the present article we make use of some of his main pedagogical works to characterize the concept of educative experience, starting with the distinction between educative experience and experience pure and simple. Whilst the fundamental dimensions of any experience are continuity and interaction, the educative experience is distinguished by the quality of these dimensions in promoting the subject's development, that is, the growth and widening of his/her previous experience. After clarifying this concept, we seek to understand its impact for the organization of an indirect teaching based on a cooperative search, and for conceptions of curriculum and the role of pupils and teacher. Still considering the centrality of the concept of educative experience, we try to unveil the deep nexus between progressive education and democratic education, whose key is the social reality of the intelligence heightened by democratic environments, apart from the nexus between education and democracy.